Continuous and scalable manufacture of amphibious energy yarns and textiles - Wei Gong (Nature Portfolio, 2019)
Textiles that can convert mechanical energy into electricity are attractive for wearable electronic devices, but application is hindered by stability, flexibility, and stretchability. Here the authors report scalable fabrication for a stretchable triboelectric yarn that is operational under water.